Convolutions of Singular Distribution Functions - Vynnyshyn, Ya. F. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We construct an example that demonstrates that natural restrictions imposed on finite convolutions of singular distributions do not guarantee the purity of the limit distribution.